Keanekaragaman Serangga Predator Pada Tanaman Bawang Merah (Studi Kasus Di Kecamatan Grong Grong Kabupaten Pidie) - Aidil Amar; Diah Fridayati; Syamratul Achwan; Mariana (Jurnal Sains Pertanian, 2024)
The exploration of predator insects in productive and non-productive shallots. Predator insects are one of the biological control agents that can suppress pest populations in shallot fields. This study aims to determine the diversity of predator insects in productive shallot fields compared to non-productive shallot fields. The determination of insect locations was conducted using a line transect method divided into three plots. Insect sampling was performed using yellow-plate traps, sweep nets, and pitfall traps. The results showed a total of 8 and 10 families of predator insects. However, the number of morpho-species of predator insects was generally higher in productive fields compared to non-productive fields, with 14 and 20 morpho-species, respectively. The results indicate that the richness, diversity, and evenness of predators in non-productive shallot fields are higher than in productive fields.